Influencing factors of air-quality perception in China: What is constructed? What is hidden? - Zeng, Xiangming; Yang, Gengjiao (Frontiers in Environmental Science, 2023)
China is known to be widely concerned about the air quality of its major cities. Nevertheless, the factors that influence air-quality perception (AQP) are still a matter of discussion. On the basis of one idea that AQP is constructed by media contact, this study assesses the effects of media contact, individualism, and health condition on AQP. Based on data of the Chinese General Social Survey (CGSS) in 2010, we build an ordered logistic regression model and introduce urban/rural dual structure and urbanization as control variables. The results show that media contact, health condition, and individualization affect AQP. The effect of media contact, however, varies depending on the media type, and the relationships between media contact and AQP change according to region when adding control variables. Health condition is significant only when it affects work and activities, as well as when mental health (MH) occurs. Additionally, the function of health effect (HE) and MH on AQP only becomes obvious in some areas after adding control variables. Moreover, in most places, the effect of some individualization variables on AQP disappear after adding control variables, whereas they continue to be obvious in others. Therefore, the effect of control variables, which are urbanization level and urban/rural dual structure, is hidden. Furthermore, there is a need to pursue economic and environmental justice between developed and undeveloped areas. The study replies with the effect of constructionism and realism on AQP. And it also sheds light on both the constructed and hidden functions of media contact.